Comparison of ease of endotracheal intubation with fixed height pillow versus pillow height attained by alignment of external auditory meatus to sternal notch - Priyanka Bansal; Pulkita Kataria; Kirti Kshetrapal; Hemant Kamal; Renu Bala; Geeta Ahlawat (Asian Journal of Medical Sciences, 2024)
Background: Endotracheal intubation is considered to be the “Gold Standard” for airway management during the administration of general anesthesia and in critical care setting because of its advantages, which allows delivery of anesthetic gases and oxygen through positive pressure ventilation without inflation of stomach, permits access to tracheobronchial tree for pulmonary hence minimizing the risk of gastric content aspiration, and improves surgical access to head and neck. The major determinants of easy tracheal intubation are optimal laryngoscopy and a good visualization of the glottis. Aims and Objectives: The aims and objectives of the study are to seek the optimal pillow height that gives the best direct laryngoscopic view and can be recommended as the starting head position before direct laryngoscopy in adults. Materials and Methods: The present study was conducted in a prospective randomized comparative manner in the Department of Anaesthesiology and Critical Care, Pt. B.D. Sharma University of Health Sciences, Rohtak after obtaining approval from the institutional ethical committee (approval number: No. BREC/Th/20/Anaesth.../034). Patients included were scheduled for elective surgery under general anesthesia requiring endotracheal intubation. The inclusion criteria were patients aged 18–50 years of either sex of ASA I and II. Results: A total of 50 subjects, 25 in each group, were included in the final analysis. Following observations and results were drawn from the present prospective and randomized study using appropriate statistical tests. The various observations were out of 50 patients in the study population, and the mean age in years of patients in Group 1 was 38.48±11.77 years and 39.36±11.64 years in Group 2. Conclusion: To conclude, alignment of external auditory meatus to sternal notch offers better conditions for endotracheal intubation than conventionally used sniffing position when assessed in terms of Cormack–Lehane grading and time taken for laryngoscopy and intubation.